Assessment of a complete truck operating under dual-mode dual-fuel combustion in real life applications: Performance and emissions analysis. (1st December 2020) - García, Antonio; Monsalve-Serrano, Javier; Lago Sari, Rafael; Gaillard, Patrick
Highlights: Near-term regulations impose stringent emissions limits for the transport sector. New vehicle technologies are necessary to reach the future emissions levels. Dual-mode dual-fuel truck concept as a possible solution to reach the limits. Euro VI NOx levels reached at engine-out conditions with 50% of truck payload. HC and CO reduced to the Euro VI normative with a conventional oxidation catalyst. Abstract: The dual-mode dual-fuel (DMDF) strategy has been demonstrated to be a potential combustion mode to cover all the engine map with low-to-moderate NOx and soot emissions and high efficiency simultaneously. This can be accomplished by modifying the injection strategy to promote a fully premixed or a dual-fuel diffusive combustion depending on the operating conditions. The main limitation of the DMDF are the high concentrations of unburned hydrocarbons and carbon monoxide coupled with low exhaust temperatures, which can be a challenge for the stock diesel oxidation catalyst (DOC). Moreover, the use of a diffusive combustion combined with high EGR rates to avoid mechanical issues at high load enhances the soot formation, which can compromise the final soot levels in a homologation cycle. To evaluate these aspects, this work studies the performance and emissions of a DMDF truck concept along a WHVC and different in-service conformity cycles through vehicle systems simulations. For both types of cycles, five payloads were tested (0%, 25%, 50%, 75% and 100%) to evaluate the impact of this parameter on the operating points distribution inside the DMDF map. The first results show that the DMDF concept provides engine-out NOx levels below the EUVI regulation at normative payload (50%) with similar fuel consumption than the conventional diesel truck. On the other hand, the engine-out HC and CO emissions exceed their respective limits in all the cases, while the engine-out soot emissions only reach the EUVI levels up to 25% payload. By this reason, the stock DOC and diesel particulate filter from the conventional diesel truck were modelled and fitted to the DMDF truck model. The results evidenced that the use of these two ATS allows to achieve the EUVI limits in terms of tailpipe HC, CO and soot independently on the cycle and payload analyzed. Moreover, considering the tailpipe emissions values achieved with ATS at 50% payload, it can be inferred that both devices could be downsized for the DMDF application as compared to the conventional ATS for diesel applications.